Solitary Metastasis of Renal Cell Carcinoma to the Adrenal Gland: Treatment Outcomes Following Laparoscopic Retroperitoneal Adrenalectomy - Cameron Parkin; George Acland; Mark Louie-Johnsun (Journal of Urological Surgery, 2021)

(untitled)
Objective:The oncological and survival benefits of adrenalectomy in patients with solitary adrenal metastasis following nephrectomy for renal cell carcinoma (RCC) through the use of a retroperitoneal laparoscopic technique are not yet known. This study aimed to report the outcomes of patients who have undergone laparoscopic retroperitoneal adrenalectomy for a solitary adrenal metastasis from primary RCC.Materials and Methods:From a prospectively collected single-surgeon database of 307 upper tract retroperitoneal laparoscopic cases, four patients underwent laparoscopic retroperitoneal adrenalectomy for solitary RCC metastasis between January 2015 and August 2020. Their clinical history, pathology, and perioperative and oncological outcomes were reviewed.Results:The mean age of the patients at initial nephrectomy was 61±10.8 years, and all had negative surgical margins. The median time to diagnosis of adrenal metastasis was 52.6 (13.6-121.0) months. In three patients, metastasis to the adrenal gland contralateral to the original nephrectomy was identified. All patients underwent retroperitoneal laparoscopic adrenalectomy, which confirmed metastatic RCC. All surgical margins were free of disease. Within 90 days post-adrenalectomy, only one Clavien-Dindo grade 1 complication was recorded. One of the patients died from widespread metastatic disease 45 months following his adrenalectomy. The remaining three patients remain cancer-free.Conclusion:Solitary metastatic adrenal recurrence from RCC is rare. To our knowledge, this is the largest study that describes a laparoscopic retroperitoneal approach in the removal of solitary adrenal metastatic RCC. This minimally invasive approach can be performed safely with low perioperative complications and encouraging oncological outcomes.